Universal Infinite Clique-Omitting Graphs: Dedicated to the memory of Professor Mahmut Bajraktarević - Džamonja, Mirna (Sarajevo Journal of Mathematics, 2024)
Dedicated to the memory of Professor Mahmut Bajraktarević The main result of the paper is that when κ is a cardinal of cofinality ω and λκ, the class of graphs of size λ omitting cliques of size κ has no universal element under graph homomorphisms (or the weak and strong embeddings). This theorem only requires ZF.